The Impact of Using Gadget in Increasing Students' Reading Comprehension in Eleventh Grade at SMA Negeri 4 Makassar - Julia I, Trigen; Batau, St. Haliah; Muliati, Muliati (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2024)
Nowadays, there are many schools, especially high schools, which allow their students bring gadget to school. Therefore, it is crusial for students to know how to use gadget as possible as they can as a helping tool especially to increase their academic skills including their reading comprehension in English lesson. The purpose of this study was to find out the use of gadget in increasing students’ reading comprehension in eleventh grade at SMA Negeri 4 Makassar in academic year 2023/2024. The sample of this study were 20 students from class XI-8. The method that was used in this study was a quantitative method with a pre-experimental design that use three steps, namely pre-test, treatment, and post-test. The findings revealed that there is an increase of students’ score in pre-test to post-test. The mean of students’ score in pre-test was 41,960 and post-test was 68,295. The t-tes was used SPSS 18 and the result is 0,000 (<0,50) which means that there is a significant difference between students’ score in pre-test to post-test. Therefore, it can be concluded that the use of gadget can increase students’ reading comprehension in eleventh grade at SMA Negeri 4 Makassar.